Number Theoretic Methods: Future Trends - Kanemitsu, Shigeru (Springer, 2002)
This book contains various topics in number theory and provides the reader with an overvierw of current and future researches in the field. Audience: Researchers and graduate students in number theory, enthusiastic amateurs and undergraduate students who have some basic knowledge in mathematics